Efficacy of Sprayers Against Pests in Paddy Crop - Nanda, S K; Behera, B K; Behera, D; Goel, A K; Pradhan, P L (Journal of Agricultural Engineering, 2008)
An experiment was conducted to study the efficacy of three sprayers, namely spinning disc type low volume sprayer, hand compression sprayer and air assisted power sprayer in controlling some commonly found pests in paddy crop. The spray characteristics revealed that the ratio of VMD to NMD was near to unity (1.06) in case of low volume sprayer followed by 1.33 in hand compression sprayer and 1.39 in power sprayer with a droplet density of 37.67, 25.67 and 21.0 numbers/cmÂ². The efficacy of the power sprayer in controlling the stem borer (Dead Heart), stem borer (White Ear Head), Leaf Folder Damaged Leaf (LFDL), Whorl Maggot (WM), White Back Plant Hopper (WBPH) and Brown Plant Hopper (BPH) was significantly (P&lt0.05) higher than low volume sprayer and hand compression sprayer with damage control of 82.90, 59.20, 88.25, 87.85, 75.30 and 92.40% respectively. Damage control of Gall Midge (Silver Shoot) did not vary significantly between power sprayer (15.30%) and hand compression sprayer (13.05%). The low volume sprayer and hand compression sprayer were found equally good to control White Ear Head (53.76% and 52.60%) and Whorl Maggot (72.45% and 68.85%). The field capacities of the sprayers were 0.08, 0.11 and 0.30 ha/h in low volume sprayer, hand compression sprayer and power sprayer respectively. The cost of spraying was found to be Rs. 65.00, Rs. 114.00 and Rs. 134.00/ha in low volume sprayer, hand compression sprayer and power sprayer respectively.